Time series analysis of SCIAMACHY and GOME-2 absorbing aerosol index in Iran - Faezeh Alizadeh; Samereh Falahatkar; Afsaneh Afzali (علوم محیطی)
Introduction: In the past three decades, dust has become a global concern for global societies. Due to Iran’s location in an arid region, it is severely influenced by this phenomenon. This phenomenon usually carries a huge mass of particle matters that can be clearly detected by satellite images. The purpose of the present study was to investigate the time series changes of absorbing aerosol index using satellite images at a national scale. Material and methods: In order to study the trend of monthly changes in dust phenomena in Iran, the data of Absorbing Aerosol Index (AAI) of SCIAMACHY sensor, which was taken during 2002-2012, and GOME-2 during 2007-2017 were evaluated using non-parametric Man-Kendall test. The variation rates for different sectors were estimated using Theil-Sen slope. Results and discussion: The results showed an increasing trend in the western, southwest, center, and northeastern regions of Iran during 10 years based on Z statistics SCIAMCHY. The results also showed an increasing trend of GOME-2 Aerosol Absorbing Index in some parts of Markazi, Isfahan, Hamedan, and Fars provinces, and Lake Urmia and completely in Chaharmahal & Bakhtiari, and Kohgilouyeh & Boyerahmad provinces. Also, Golestan and Semnan provinces didn’t show any specific trends. According to P statistic, the trend of change in most regions of Iran was significant. Based on the results of Theil-Sen slope, the western, southern and central regions of Iran showed the most changes in atmospheric aerosol concentration. Conclusion: The high compatibility between the present results and the reports of meteorological stations showed the high capability of satellite data, which we used in this study, in order to identify the areas that encountered to dust phenomenon at a national scale. Accordingly, it is recommended that this technology be used for the macro-management of the natural resources in Iran.